1985
DOI: 10.1084/jem.161.2.392
|View full text |Cite
|
Sign up to set email alerts
|

Serum factor requirement for reactive oxygen intermediate release by rabbit alveolar macrophages.

Abstract: Alveolar macrophages (AM) from pathogen-free rabbits were unable to release reactive oxygen intermediates (ROI) unless they were conditioned in serum for 24-48 h before triggering with membrane-active agents. The degree of serum conditioning of AM depended upon the concentration of serum used; optimal ROI release was obtained at or above 7.5% fetal bovine serum (FBS). FBS, autologous rabbit serum, pooled rabbit serum, and pooled human serum were each capable of conditioning AM for release of ROI. Serum conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Most probably the endotoxin level in FBS already exceeded the sensitivity threshold of Kupffer cells, above which they do not respond in a dose-dependent fashion to lipopolysaccharide. Similarly, Gerberick et al [10] were unable to demonstrate any enhancing action of lipopolysaccharide on the ability of serum-conditioned alveolar macrophages to produce superoxides. The addition of lipopolysaccharide to Kupffer cells from germ-free C3H mice did augment IFN production (Table 5B).…”
Section: Discussionmentioning
confidence: 96%
“…Most probably the endotoxin level in FBS already exceeded the sensitivity threshold of Kupffer cells, above which they do not respond in a dose-dependent fashion to lipopolysaccharide. Similarly, Gerberick et al [10] were unable to demonstrate any enhancing action of lipopolysaccharide on the ability of serum-conditioned alveolar macrophages to produce superoxides. The addition of lipopolysaccharide to Kupffer cells from germ-free C3H mice did augment IFN production (Table 5B).…”
Section: Discussionmentioning
confidence: 96%
“…Although these cell lines provide the convenience of spontaneous replication and functional homogeneity, they differ from normal macrophages in several important aspects, such as expression of Ia antigen, adherence to various surfaces, and production of inflammatory cytokines (3)(4)(5)7). Such cell lines also display varying dependence on culture media supplemented with serum and additional growth factor(s) (3,13,16) which are known to have effects on normal macrophage function (1,10,11,21). Even in those cell lines that retain some membrane markers and functions characteristic of normal macrophages, subtle differences exist in their state of activation or their response to activating stimuli.…”
Section: Letter To the Editor Cryopreserved Normal Macrophages As A Cmentioning
confidence: 97%
“…The induction and assay of 02 -release performed as reported by Gerberick (10,11) was based on the demonstration that whereas resident rabbit AM release minimal 02-when triggered in vitro with membrane-active agents, they can be conditioned in a dose-dependent manner for greatly enhanced O2-release by activating in the presence of serum or plasma for 24-48 h before triggering with phorbol myristate acetate (PMA) and measured by reduction of ferricytochrome-c in the presence of nitroprusside. IL-1 activity was measured by a thymocyte costimulation assay as described by Simon and Willoughby which was based on the uptake of [3H]thymidine in response to IL-1 stimulation (22).…”
Section: Letter To the Editor Cryopreserved Normal Macrophages As A Cmentioning
confidence: 99%
“…These lymphokines could have several in vivo effects. It has been shown that they can increase vascular permeability [23] and, therefore, cause the transudation of plasma components known to prime macrophages [24,25], or they can prime the macrophages directly [26]. It also seems that T lym phocytes are involved in the process of goblet cell metaplasia and that lymphokines stimulate goblet cell mucus production [27,28].…”
Section: Discussionmentioning
confidence: 99%